Impacts of rural worker migration on ambient air quality and health in China: From the perspective of upgrading residential energy consumption. (April 2018) - Shen, Huizhong; Chen, Yilin; Russell, Armistead G.; Hu, Yongtao; Shen, Guofeng; Yu, Haofei; Henneman, Lucas R.F.; Ru, Muye; Huang, Ye; Zhong, Qirui; Chen, Yuanchen; Li, Yufei; et al.
Abstract: In China, rural migrant workers (RMWs) are employed in urban workplaces but receive minimal resources and welfare. Their residential energy use mix (REM) and pollutant emission profiles are different from those of traditional urban (URs) and rural residents (RRs). Their migration towards urban areas plays an important role in shaping the magnitudes and spatial patterns of pollutant emissions, ambient PM2.5 (fine particulate matter with a diameter smaller than 2.5 μm) concentrations, and associated health impacts in both urban and rural areas. Here we evaluate the impacts of RMW migration on REM pollutant emissions, ambient PM2.5, and subsequent premature deaths across China. At the national scale, RMW migration benefits ambient air quality because RMWs tend to transition to a cleaner REM upon arrival at urban areas—though not as clean as urban residents'. In 2010, RMW migration led to a decrease of 1.5 μg/m 3 in ambient PM2.5 exposure concentrations ( C ex ) averaged across China and a subsequent decrease of 12, 200 (5700 to 16, 300, as 90% confidence interval) in premature deaths from exposure to ambient PM2.5 . Despite the overall health benefit, large-scale cross-province migration increased megacities' PM2.5 levels by as much as 10 μg/m 3 due to massive RMW inflows. Model simulations show that upgrading within-city RMWs' REMs can effectively offset the RMW-induced PM2.5 increase in megacities, and that policies that properly navigate migration directions may have potential for balancing the economic growth against ambient air quality deterioration. Our study indicates the urgency of considering air pollution impacts into migration-related policy formation in the context of rapid urbanization in China. Highlights: RMW migration is upgrading residential energy use in China. 13, 000 (7000–17, 000) deaths were avoided in 2010 because of RMW migration. RMW migration increases health burdens from air pollution in megacities. Improving RMWs' energy infrastructure is beneficial to air quality in megacities.